Toponymy and word association: a cognitive linguistic approach to enhancing English vocabulary acquisition - Nenotek, Seprianus A; Charity Onyishi (Mell Baou Publisher, 2025)
This article presents a literature-based inquiry exploring the potential of toponymy—the study of place names—as a medium for English vocabulary acquisition. Specifically, it examines how toponymy can be effectively utilized through the word association strategy, rooted in cognitive linguistic theory. This approach shifts vocabulary learning from rote memorization to a cognitively enriched process, emphasizing the formation of meaningful semantic networks within learners’ mental lexicons. Place names such as “London,” “Amazon,” or “Himalaya” carry semantic and cultural associations that naturally stimulate word connections—nouns, adjectives, idioms, and cultural imagery—that enhance vocabulary breadth and depth. Drawing on theoretical frameworks and previous studies, this paper argues that integrating toponymy into language instruction improves not only vocabulary retention but also learners’ cultural and geographical awareness. The strategy aligns with contextual and communicative language teaching approaches, which underscore the importance of authentic and meaningful language use. As such, toponymy emerges as a promising pedagogical tool for fostering richer, more engaging vocabulary learning experiences.